Exercise and Physical Functioning in Osteoarthritis Medical, Neuromuscular and Behavioral Perspectives - Dekker, Joost.; Dekker, Joost. (SpringerBriefs in Specialty Topics in Behavioral Medicine,, 2014)
Osteoarthritis (OA) is among the top 10 of most disabling diseases in the Western world. It is the major cause of pain and disability among the elderly. This book provides a contextual review of recent research on neuromuscular factors and behavioral risk factors for functional decline in OA, with a special emphasis on explanatory mechanisms. In addition, the book discusses innovative approaches to exercise and physical activity in OA, derived from research on behavioral and neuromuscular risk factors for functional decline in OA. Recent research has shown that neuromuscular factors (such as muscle strength, joint laxity) and behavioral factors (such as avoidance of activity, depressed mood) predict pain and disability in OA. Furthermore, exercise and physical activity are among the dominant interventions aiming at reducing pain and disability, and innovative interventions targeting neuromuscular and behavioral interventions have been recently developed. This research has been published as separate papers, with the result that the field is in need of an integrative contextual review that puts the research into theoretical perspective.